Nutritional insufficiency and therapy for cancer patients. Modern view on the problem - E. V. Gameeva; V. E. Khoronenko; M. M. Shemetova (Сибирский онкологический журнал, 2020)
Background. Metabolic changes due to the progression of cancer and its aggressive treatment, lead to decreased food intake, related with development of cancer anorexia-cachexia syndrome (CACS) because of the complex interactions between pro-inflammatory cytokines and host metabolism. Beyond the physical and the metabolic consequences, cancer patients are often suffering from psychological distress, including depression.Material and Methods. A literature search and analysis of data was conducted in PubMed and Medline databases since 2000 with the purpose to evaluate the effectiveness of additional oral methods of nutritional support for cancer patients.Results. Nutritional support has a positive effect on response to cancer therapy and reduces the incidence of complications by optimizing the balance between energy expenditure and food consumption. In palliative care, nutritional support aims at improving patient’s quality of life by controlling symptoms such as nausea, vomiting and pain related to food intake.Conclusion. The literature review confirms that nutritional intervention has a direct impact on quality of life and should be integrated into the global cancer care because of its significant contribution to QoL. Furthermore, monitoring and correction of nutritional status should be an integral part of the quality of life assesses with the aim to optimize its adequacy to the patient’s needs and expectations.